2009
DOI: 10.1016/j.biomaterials.2008.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Preferential cell attachment to nitrogen-doped diamond-like carbon (DLC:N) for the measurement of quantal exocytosis

Abstract: Electrochemical measurement of transmitter or hormone release from individual cells on microchips has applications both in basic science and drug screening. High-resolution measurement of quantal exocytosis requires the working electrode to be small (cell-sized) and located in immediate proximity to the cell. We examined the ability of candidate electrode materials to promote the attachment of two hormone-secreting cell types as a mechanism for targeting cells for to recording electrodes with high precision. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…It is more transparent than boron-doped NCD and works nicely in the anodic regime (Sun and Gillis, 2006). However, ITO shows a lower chemical stability, especially at acidic pH and cathodic potentials, and a narrower potential window with respect to the ∼3 V of boron-doped NCD electrodes (Sun and Gillis, 2006;Chen et al, 2008;Sen et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…It is more transparent than boron-doped NCD and works nicely in the anodic regime (Sun and Gillis, 2006). However, ITO shows a lower chemical stability, especially at acidic pH and cathodic potentials, and a narrower potential window with respect to the ∼3 V of boron-doped NCD electrodes (Sun and Gillis, 2006;Chen et al, 2008;Sen et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore carbon-fiber electrodes are pressed gently to the surface of the cell whereas it is desirable for cells to tightly adhere to planar electrodes so they do not wash away upon solution exchange 1314 . Gleixner and Fromherz 31 measure the sheet resistance (R sheet ) between adherent cells and a fibronectin-coated silica substrate to be ~10 MΩ in physiological bath solution.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings provide evidence that reducing inflammatory cell adherence using antifouling coatings, like pHEMA, can reduce the accumulation of glia surrounding devices implanted into the CNS. Whilst, other studies have reported similar low levels of inflammatory cell adherence (monocytes and macrophages) using antifouling agents [8,25,36], we have presented the additional possibility of spatially controlling this effect using our micropatterned PEG surfaces. We believe that by doing so, we can tailor implants that make use of the beneficial effects of the foreign body response (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…Diamond-based coatings have also been shown to improve haemocompatability (by reducing activation of the coagulation cascade, platelets and inflammatory cells) [18][19][20][21][22][23]. Furthermore, diamond and DLC can be modified with dopant materials to alter their mechanical, chemical, electrical and biological properties [24][25][26][27][28][29]. For example, boron-doping vastly increases the electrical conductivity of diamond, making it more suitable for electrode applications [24].…”
Section: Introductionmentioning
confidence: 99%